Job Satisfaction and Commitment in The Era of Decentralization: Case Study of Family Planning Design - Parianti, Andi; Bin Yaacob, Hashim Fauzy (Universitas Muhammadiyah Metro, 2017)
Implementation of law number 22 in the year of 1999 on regional autonomy has changed the management of government of Indonesia, both on the national scale and on a regional one. One of thegovernment institutions that got its impact is Family Planning Program. This program has implications, not only to advisor’s attitudes and work behaviors, such as job performance and working motivation but also to government commitment on the reception and implementation of this program namely formation of family planning institutions at theregional level.One of the attitudes indicated by the advisor in the form of complaints related to salary wages and operating costs are not considered balance with the workload that causes themotivation and performance of work decrease. Other phenomena are to turn over the workers in the family planning and other government institutions. Accumulation of these could be the cue of advisors’ weak commitment towards their institutions. Implications: This study can provide an understanding of job satisfaction and increase the extension's commitment in performing its duties.